Pengaruh Level Voltase Electrical Waterbath Stunning Terhadap Sifat Fisik Daging Ayam Broiler - Prastyawan, Fiky Andy; Suryanto, Edi; Erwanto, Yuny (Jurnal Teknologi Hasil Peternakan, 2023)
Stunning is a way to comply with animal welfare standards. Stunning method is effective if the poultry temporarily loses consciousness and does not die. This study aims to determine the effect of the electrical waterbath stunning method with different voltages on the physical properties (pH, Water Holding Capacity, Cooking Loss and Tenderness) of broiler chicken meat. This research was conducted experimentally based on a completely randomized design (CRD) with unidirectional patterns with 3 different voltages, namely P0 (0V), P1 (40V), P2 (50V) and P3 (60V) with frequency 50 Hz currents of 0.5 A and soaking time for 5 second. with 3 repetitions. The data obtained was analyzed by Analysis of Variance (ANOVA) and if there was a significant difference, Duncan's further test was carried out. The results showed that the use of different voltages in the electrical waterbath stunning had no effect (P>0.05) on the physical properties of broiler meat. In this study, the average meat pH was in the range of 5.88-5.98, water holding capacity in the range of 25.39-25.50%, cooking losses in the range of 25.29-25.51% and tenderness in the range of 2.32-2.44 kg. /cm2 . In conclusion the stunning voltages levels did not affect the physical quality of broiler meat